Klasifikasi Penyakit Daun Padi Berdasarkan Hasil Ekstraksi Fitur GLCM Interval 4 Sudut - Jani Kusanti; Noor Abdul Haris (Politeknik Harapan Bersama, 2018)
One of the factors causing rice production depression is a typical disease in rice plants. Typical of disease in rice plants, among others, such Blast Disease, Leaf Blight Disease, Disease Hawar On Stem, Crackle Disease and so on. Each type of disease requires different treatment, but not all farmers know the type of disease so as to allow for errors in the handling. This research made an application program that can identify rice pests to facilitate farmers solve the problems of rice plants disease since it becomes important to make a disease classification system on the leaves of rice plants. This research uses backpropagation method to classify the type of disease resulting from feature extraction of GLCM with 4 angles. Results obtained 80% accuracy from 30 data, with 16 seconds testing time.